Magmatism at an ultra-slow spreading rift: high-resolution geomorphological studies of a Red Sea Rift segment in Hadarba Deep - Le Saout, Morgane; van der Zwan, Froukje M.; Schiebener, Cora K.; Augustin, Nico (Frontiers in Marine Science, 2023)
The mid-ocean rift in the Red Sea is one of the youngest rifting systems on Earth. Only recently, state-of-the-art methods and modern deep-sea instruments have been used to explore this young and unique volcanic system. During the first autonomous underwater vehicle surveys of the Red Sea Rift in Spring 2022, we collected multibeam bathymetry, backscatter, sub-bottom profiler data, and water column data over a 9 km long ridge segment in the Hadarba Deep between 22.49°N and 22.56°N to investigate the volcano-tectonic processes of this ultra-slow spreading segment (12 mm/year spreading rate). The high-resolution hydroacoustic data was used to (1) delineate and quantify the geometry of tectonic structures and individual lava flows, (2) define lava flow morphology and eruption style, (3) estimate relative ages of flows and features, and (4) retrace the evolution of the volcanic activity. In addition, the geochemistry of several young lava flows provides information on the relation between the different magma that supply these eruptions. About 90 eruptive units with variable sedimentary cover have been identified within the 43 km2 mapped region. The oldest lava flows are buried under 3 to 4.2 m of sediment, indicating ages of up to ~30 ka based on average sedimentation rate estimates (~14 cm/ka), while the youngest eruptions are covered by<10 cm of sediment, and are thus younger than 700 years. Three volcanic phases have been identified based on changes in flow morphology and distribution, and tectonic pattern. All three axial phases have an average eruptive frequency of ~100-250 years. The segment displays an overall low tectonic extension (<10% of the total extension) and low vertical offset. Our geomorphological maps, analyses, and statistics reveal a moderately faulted, ultra-slow spreading MOR segment in the Red Sea with a surprisingly large amount of magmatic extension, implying that the segment has been underlined by a large magma supply for at least 15 ka. All these observations provide valuable implications for the formation history of the Red Sea Rift and the formation of ultra-slow spreading crust.